Posisi Perempuan dalam Kewarisan Adat Jambi Indonesia - Hidayati, Rahmi; Ramlah, Ramlah; Maryani, Maryani; Prawira, Ilham Abdi; Asiyah, Asiyah (Lembaga Penelitian dan Pengabdian pada Masyarakat, Institut Agama Islam Negeri (IAIN) Kerinci, Jambi, 2024)
This research aims to determine women’s position in the distribution of inheritance in the Merangin Jambi community. This research uses social and legal research methods to understand legal phenomena from the social and cultural context in which the law exists. The primary data for this research comes from in-depth interviews with religious and traditional leaders. In contrast, secondary data is obtained from relevant literature.. The data is then analyzed through editing, organizing and grouping research results. The research result In the Merangin Jambi custom, women are the place where men’s families return when they are in trouble or disaster. This can be seen in the dominant position of women in the distribution of inheritance. There is no difference in principles between men and women in the distribution of inheritance, they have the same rights with consideration of the common good.